The rubric of self-evaluation as a didactic strategy for writing reviewing - Calle-Álvarez, Gerzon Yair (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article shows the results of a research whose objective was to analyze the application of a self-evaluation rubric as a didactic strategy for writing reviewing. For this, a case study was applied and the sample was made up of 195 self-assessments of the writing productions of high school students, generated during the virtual writing workshops guided by the tutors of an Online Writing Center, in an educational institution of Medellin, Colombia. The self-assessed typologies were the essay, the academic presentation and the review. The results show a good level of reliability according to Cronbach's Alpha and the standard deviation reflects the differences associated with the levels of appropriation of writing by students. The conclusions state that the instrument can be used didactically in face-to-face or virtual academic activities. In addition, the use of self-assessment as a writing review strategy favors the students being autonomous and self-reflective of their textual production.